MADRASAH SEBAGAI LEMBAGA PENDIDIKAN ISLAM YANG IDEAL - Nauval Ardian Saputra; Vinka Farqiyah; Siti Nur Maulidiyah Munandari; M.Yunus Abu Bakar (Cahaya Ilmu Bangsa Institute, 2024)
Madrasah is an Islamic educational institution that plays a significant role in the development of education in Indonesia. The philosophy of madrasah integrates both religious and general education, aiming to produce a generation that possesses not only academic knowledge but also good morals. In this context, madrasah serves as a means to instill Islamic values and prepare students to face the challenges of modern times. Thus, madrasah functions not only as a formal educational institution but also as a moral and spiritual pillar of society. This article demonstrates that madrasah has great potential to continuously focus on its essence, ideal foundations, and ideal designs so that madrasah in Indonesia can continue to evolve into an excellent educational institution that positively contributes to the character building and spirit of the nation.